SENGKETA KEPEMILIKAN TANAH ANTARA PT. KERETA API INDONESIA (KAI) DENGAN MASYARAKAT YANG MENGUASAI LAHAN FISIK: STUDI PENGADILAN NEGERI MEDAN NOMOR 300/Pdt/G/2017/PN.MDN - Rahma Dewi, Novia; Purba, Hasim; Sembiring, Rosnidar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Every land dispute requires resolution, either through litigation or non-litigation. Non- litigation dispute resolution is also known as an alternative, out-of-court solution that provides legal certainty in a cost-effective, efficient, and faster manner that benefits both parties. This study discusses How to Resolve Land Disputes Owned by PT Kereta Api Indonesia Seized by the Community in a Civil Law Perspective? What are the Pros and Cons of Communities in Land Disputes with PT KAI? How is the Analysis of the Judge's Legal Considerations on the Settlement of Land Disputes Between PT.KAI and the Community (Study of Medan District Court Decision Number 300 / Pdt / G / 201/ PN.Mdn. The research method used in this study uses normative legal research. The results of this study The settlement of land disputes between PT.KAI and the community can be done first with mediation efforts before the court realm, the Government as the main regulator in railway transportation needs to facilitate dialogue between the railway (operator, management) and the community. This can be in the form of discussion forums, mediation, or even face-to-face meetings. Community Involvement: Educating the community about train operational procedures. The community also needs to be given an understanding of their responsibilities as users of train services, for example about the importance of following safety and discipline rules when at the station or on the train. Independent Supervision: The community can invited to participate in monitoring public facilities such as railway lines to reduce undesirable incidents.